Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics: System Demonstrations 2020
DOI: 10.18653/v1/2020.acl-demos.31
|View full text |Cite
|
Sign up to set email alerts
|

ADVISER: A Toolkit for Developing Multi-modal, Multi-domain and Socially-engaged Conversational Agents

Abstract: We present ADVISER 1 -an open-source, multi-domain dialog system toolkit that enables the development of multi-modal (incorporating speech, text and vision), sociallyengaged (e.g. emotion recognition, engagement level prediction and backchanneling) conversational agents. The final Python-based implementation of our toolkit is flexible, easy to use, and easy to extend not only for technically experienced users, such as machine learning researchers, but also for less technically experienced users, such as lingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…e early development of chatbot was mostly dominated by a single domain. It has been observed that more research has been directed towards open domain [45][46][47][48][49] and multidomain [50][51][52] in recent years. Single-domain chatbots are limited to accomplishing specific tasks, while multidomain or open domain chatbots can better meet the needs of smart assistants and even further provide people's companionship or social applications.…”
Section: Discussionmentioning
confidence: 99%
“…e early development of chatbot was mostly dominated by a single domain. It has been observed that more research has been directed towards open domain [45][46][47][48][49] and multidomain [50][51][52] in recent years. Single-domain chatbots are limited to accomplishing specific tasks, while multidomain or open domain chatbots can better meet the needs of smart assistants and even further provide people's companionship or social applications.…”
Section: Discussionmentioning
confidence: 99%
“…Designing multimodal systems is becoming increasingly more feasible than ever with many tools and frameworks being developed. Most of them are online available via public repositories (Bohus et al, 2017;Michael, 2020;Li et al, 2020). However, many dialogue designers still struggle with the complexity of building social conversational agents.…”
Section: Discussionmentioning
confidence: 99%
“…An editor for modifying template files in a tree-like structure would benefit less technically apt dialogue designers. Nevertheless, we see Flipper as a more abstract dialogue management system, connected to external components that each have their own authoring interfaces that help dialogue designers in prototyping a specific component, such as the user simulations in ADvISER (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations